Analisis Pengaruh Faktor Lokasi, Harga Dan Kelengkapan Produk Terhadap Niat Pembelian Ulang Konsumen (Kasus Pada Alfamart Garuda Mas Surakarta) - Widyaswara, Tika Hayuning, Drs.Sri Padmantyo,MBA (2016)
This study aims to determine the effect of location, price and completeness of the product to the consumer repeat purchase intentions. This study uses a quantitative research, using descriptive methods. The population in this study are all the people who come to shop in Alfamart. Sample in this study were 150 people who came to shop in Alfamart. Analysis of the data in this study using multiple linear regression, it is used to determine the effect of variable location (X1), Fittings Products (X2), and price (X3) on Repeat Purchase intentions Consumer (Y). Based on the survey results revealed that the value of the result of the location of 4.761 tcount variable, the variable price of 3,239 and variable Product Completeness of 6.609 and the value table = 1.976, this means that thitung> ttabel¬ then Ho is rejected so that there is a significant effect Location, Price and Fittings products on Consumer Purchase Intentions Birthday individually.